2018
DOI: 10.1111/1541-4337.12346
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Antimicrobial Activities of (‐)‐Epigallocatechin‐3‐gallate (EGCG) and its Potential to Preserve the Quality and Safety of Foods

Abstract: Quality deterioration of fresh or processed foods is a major challenge for the food industry not only due to economic losses but also due to the risks associated with spoiled foods resulting, for example, from toxic compounds. On the other hand, there are increasing limitations on the application of synthetic preservatives such as antioxidants in foods because of their potential links to human health risks. With the new concept of functional ingredients and the development of the functional foods market, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(83 citation statements)
references
References 223 publications
(288 reference statements)
2
79
1
1
Order By: Relevance
“…Shin et al (2017) found that coating solution containing apple peel powder reduced lipid oxidation in beef patties. The presence of hydroxyl groups on the aromatic rings of phenolic compounds are associated with their antioxidant activity through donating electrons and neutralize free lipid radicals generated during the initial stage of oxidation (Medina et al 2007;Nikoo et al 2018). This further inhibits their degradation to more active oxidizing agents, such as MDA (Radha Krishnan et al 2013) that may explain the inhibition of lipid oxidation.…”
Section: Lipid Oxidationmentioning
confidence: 99%
“…Shin et al (2017) found that coating solution containing apple peel powder reduced lipid oxidation in beef patties. The presence of hydroxyl groups on the aromatic rings of phenolic compounds are associated with their antioxidant activity through donating electrons and neutralize free lipid radicals generated during the initial stage of oxidation (Medina et al 2007;Nikoo et al 2018). This further inhibits their degradation to more active oxidizing agents, such as MDA (Radha Krishnan et al 2013) that may explain the inhibition of lipid oxidation.…”
Section: Lipid Oxidationmentioning
confidence: 99%
“…There are polyphenols, flavonoids such as flavanols (catechins, procyanidins), flavonos (rutin, quercetin, kaempferol) and phenolic acids (gallic, caffeic) (Gramza-Michałowska et al 2016 ; Lorenzo and Munekata 2016 ). Most of the total polyphenol content is constituted by catechins (85%), mainly: (+)-catechin (C), (−)-epicatechin (EC), (−)-gallocatechin (GC), (−)-epicatechin gallate (ECG), (−)-epigallocatechin (EGC) and (−)-epigallocatechin gallate (EGCG) (Oliveira 2012 ; Nikoo et al 2018 ). Green tea polyphenolic catechins inhibit growth of a wide spectrum of Gram-positive and Gram-negative bacteria species with moderate potency (Taylor et al 2005 ) and also demonstrate antioxidant activity (Gramza et al 2005a ; Saito et al 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bakteri hücre zarının seçici geçirgen özellikte ve hasar görmemiş olması, mikroorganizmaları antibakteriyel etkiden korumaktadır. Flavonollar, sitoplazmik membran fonksiyonlarını veya enerji metabolizmasını inhibe ederek etkili olurken [48], kateşinler ise, yüzey proteinleriyle etkileşime girerek ve/veya H2O2 oluşturarak bakteri hücrelerine oksidatif strese sokmakta [49], antosiyaninler ise, hücre zarına zarar verdiğinden protein ve nükleik asit kaybına neden olmakta, adenozin trifosfataz (ATPaz), süper oksit dismutaz (SOD) gibi enzimlerin daha düşük aktivite göstermesine neden olarak patojenlerin gelişmesini engellemektedir [23,25,28,50].…”
Section: Materyal Ve Metotunclassified